2014
DOI: 10.7589/2013-04-090
|View full text |Cite
|
Sign up to set email alerts
|

Acute Die-off of Chamois (Rupicapra rupicapra) in the Eastern Austrian Alps due to Bacterial Bronchopneumonia withPasteurellaceae

Abstract: ABSTRACT:Monitoring circulating pathogens in wildlife populations is important in evaluating causes and sources of disease as well as understanding transmission between wild and domestic animals. In spring 2010, a sudden dieoff in a chamois (Rupicapra rupicapra) population sharing habitat with livestock occurred in northeastern Austria. Nineteen animals were submitted for examination. Necropsy and pathohistologic and bacteriologic results yielded lesions associated with Pasteurellaceae species. Additional test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…We found that the only HS case of similar magnitude in wild or domestic ungulates was also recorded in saigas (in 1988). Parasite loads associated with one case (Posautz et al 2014) Tick-borne fever increases susceptibility to M. haemolytica cytotoxin (Woldehiwet et al 1993) Note: Mongolian gazelle cases listed under HS but in fact the syndrome is unidentified. Often restricted to single herds and a limited spatial range, both the numbers dead and mortality rates tend to be low, even in dense populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that the only HS case of similar magnitude in wild or domestic ungulates was also recorded in saigas (in 1988). Parasite loads associated with one case (Posautz et al 2014) Tick-borne fever increases susceptibility to M. haemolytica cytotoxin (Woldehiwet et al 1993) Note: Mongolian gazelle cases listed under HS but in fact the syndrome is unidentified. Often restricted to single herds and a limited spatial range, both the numbers dead and mortality rates tend to be low, even in dense populations.…”
Section: Discussionmentioning
confidence: 99%
“…In saigas, while an organism described as P. haemolytica was isolated in the 1984 outbreak (Aikimbaev et al 1985), it is not clear whether other pathogens were not involved or not detected. & Coccidia (Posautz et al 2014) and the two cases of bronchopneumonia in reindeer (listed in Table 1) infected with Hypoderma tarandi, Dictyocaulus vivparus, or Cephenomyia trompe (Skjenneberg 1957, Kummeneje 1976). One of the pasteurellosis cases in Mongolian gazelles has also been associated with a viral infection (Dash and Sokolov 1986; see Appendix S2iii).…”
Section: The Saiga Antelope: Ecology and Life Historymentioning
confidence: 99%
See 2 more Smart Citations
“…Out of 74 lung affections, with lesions characteristic of Pasteurellaceae (in particular fibrinous pleuropneumonia in apical lobes associated to pleural exudation); M. haemolytica was the causative agent in 51 cases, and P. multocida in 23 cases. Strains of Mannheimia, generally identified with biochemical methods, it is likely, on the basis of what is reported by some researchers (Villard et al, 2006;Posautz et al, 2014), that a certain proportion may correspond to the T biotype, recently reclassified as Pasteurella trehalosi. Pasteurellosis, both for domestic and wild ruminants, can be fatal in severe or complicated cases, when the lesions involve more of the lung tissue, over the classical localization in apical lobes.…”
Section: Parasitological Examination Of Faecesmentioning
confidence: 99%